RESPON STEK PUCUK JATI (Tectona grandis L.) TERHADAP PEMBERIAN ZAT PENGATUR TUMBUH BERBAHAN ALAMI - Novian S Mauguru; Mamie E Pelondo'u; Wilhelmina K. Seran (Wana Lestari, 2019)
Teak is a plant that has many benefits from roots to leaves. Various benefits of teak causing to do cultivation. One of propagation activities that often carried out was vegetative. Vegetative propagation of plants can be done by shoot cutting. Using of growth regulator with coconut water and shallots extract is expected to spur the growth in teak shoot cutting. The purpose of this study is to determine whether there is a response of teak shoots (Tectona grandis L.) to the administration of growth regulators made from natural ingredients. The research is a quantitative type using an experimental method with randomized blok design with 7 treatment, 3 replications and divided into 3 groups the size of cuttings. This research was conducted for 4 months in a greenhouse, faculty of agriculture at the University of Nusa Cendana. The results obtained showed that the administration of growth regulators made from natural ingredients had a significant effect on teak shoot cuttings. The treatment of 75% coconut water is the best treatment to be applied to teak shoot cutting.